High flow oxygen therapy versus conventional oxygen therapy in dogs and cats undergoing bronchoscopy and bronchoalveolar lavage: a pilot study - Dartencet, Camille; Abunemeh, Maha; Junot, Stephane; Nectoux, Alexandra; Allaouchiche, Bernard; Krafft, Emilie; Pouzot-Nevoret, Celine (Frontiers in Veterinary Science, 2024)
Objectives: To evaluate the safety and feasibility of high flow oxygen therapy (HFOT), and to record SpO2 and desaturation episodes in dogs and cats receiving HFOT or conventional oxygen therapy (COT) during bronchoscopy ± bronchoalveolar lavage (BAL).Materials and methods: Dogs and cats undergoing bronchoscopy ± BAL between January and May 2023 were included in the study. Patients were randomly allocated to two groups: HFOT (HFOT group; two cats and four dogs) and COT (COT group; one cat and four dogs). HFOT and COT were started at the beginning of the bronchoscopy. HFOT was delivered with a gas flow rate of 1 L/kg/min at an FiO2 of 100% and a temperature of 34°C (pediatric mode) or 37°C (adult mode). COT was delivered through the working channel of the bronchoscope at a rate of 1.5 L/min. The safety and feasibility of HFOT were assessed, and peripheral oxygen saturation (SpO2) was measured by pulse oximetry every 30 seconds throughout the procedure. Measurements and main results: HFOT was feasible and safe in both dogs and cats with no complications reported. While there was no significant difference in the number of desaturation episodes (SpO2 < 94%) between the two groups, none of the patients in the HFOT group experienced severe desaturation (SpO2 < 90%). In contrast, two patients in the COT group had an SpO2 < 90%. Mean SpO2 was significantly higher in the HFOT group compared to the COT group at T0 (98% ± 2% vs 94% ±2%), T0.5 (98% ± 2% vs 94% ± 3%) and T1 (98% ± 2% vs 94% ± 4 %).To the authors' knowledge, this is the largest study conducted to date using HFOT during bronchoscopy in dogs and cats. Our results suggest that HFOT is feasible and safe during bronchoscopy ± BAL. Furthermore, HFOT may reduce the risk of desaturation episodes in dogs and cats undergoing bronchoscopy and BAL.